2003
DOI: 10.1037/0022-006x.71.2.292
|View full text |Cite
|
Sign up to set email alerts
|

The effects of depressed mood on smoking cessation: Mediation by postcessation self-efficacy.

Abstract: This study evaluated the relationship between precessation depressed mood and smoking abstinence and assessed the mediation of this effect by postcessation self-efficacy, urges to smoke, nicotine withdrawal, and coping behavior. The sample included 121 smokers previously treated in a randomized controlled trial involving behavior therapy and the nicotine patch. The results showed that precessation depressed mood was inversely related to 6-month abstinence. This effect remained significant after controlling for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
113
3
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(133 citation statements)
references
References 59 publications
(68 reference statements)
16
113
3
1
Order By: Relevance
“…A recent review and meta-analysis found that past major depression was associated with a statistically significant, but modest, decrease in both short-and long-term abstinence rates [13]. Having experienced depression and pre-cessation depressed mood have also been found to be associated with increased relapse [14,15]. In older smokers (not all of whom were attempting to quit), level of depression predicted continued smoking [11], and there is evidence across all ages that the negative effect of depression on cessation is stronger for women [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review and meta-analysis found that past major depression was associated with a statistically significant, but modest, decrease in both short-and long-term abstinence rates [13]. Having experienced depression and pre-cessation depressed mood have also been found to be associated with increased relapse [14,15]. In older smokers (not all of whom were attempting to quit), level of depression predicted continued smoking [11], and there is evidence across all ages that the negative effect of depression on cessation is stronger for women [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Although conflicting evidence exists regarding the relationship between having a history of MDD and smoking cessation outcomes (Covey, 2004;Hall, 2004;Hitsman, Borrelli, McChargue, Spring, & Niaura, 2003), depressive symptoms ) and negative moods (Cinciripini et al, 2003;Ginsberg, Hall, Reus, & Muñoz, 1995;Killen et al, 1996;Kinnunen, Doherty, Militello, & Garvey, 1996) have been consistently associated with poorer smoking outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Smokers with depression are more likely to relapse from a quit attempt, have higher nicotine dependence, suffer negative mood symptoms from withdrawal, and suffer greater smoking-related morbidity and mortality than the general population of smokers. [6][7][8][9][10][11][12] For the general population, effective smoking cessation interventions include nicotine replacement therapy (NRT), 13 antidepressants bupropion and nortriptyline, 14 nicotine receptor partial agonists varenicline, 15 and smoking cessation counseling. [16][17][18] Pharmacological and behavioral strategies increase the likelihood of successful quits attempt by 1.5 to 2 times compared to placebo or usual care.…”
mentioning
confidence: 99%
“…19 Depression status may influence patients' ability to engage in smoking cessation. 6,7,9 Some evidence supports that smokers with current depression are less likely to succeed with smoking cessation compared to history positive patients.…”
mentioning
confidence: 99%